Clinical Biochemistry Markers in Early Detection of Cardiovascular Diseases - Rasheed, Zahraa Ali Abbas; Mankhi, Saad Jameel Shiesh; Abbas, Abdullah Hassan Hussein; Aneed, Riyadh Shamkhi Shlaka (American Journal of Biomedicine and Pharmacy, 2025)
Despite concerted efforts to prevent and reduce cardiovascular disease (CVD), CVD remains a leading cause of morbidity and mortality worldwide. In 2019, 697 000 people died of heart disease in the United States alone. The evidence base for controlling traditional CVD risk factors (hypertension, hypercholesterolemia, diabetes, lifestyle modification, and smoking) is well established, but significant research has been directed to studying additional tools, such as novel biomarkers and imaging techniques. Cardiovascular disease risk assessment using comprehensive biomarker analysis holds promise as a more effective approach for stratifying those at high risk for CVD. Atherosclerotic cardiovascular disease (ASCVD) accounts for a large proportion of the CVD burden, characterized by lipid accumulation in the arterial wall, inflammatory response, oxidative stress, and endothelial dysfunction. As a result, lipoproteins, inflammatory biomarkers, oxidative biomarkers, and endothelial dysfunction biomarkers have been proposed as additional tools to predict CVD. Hormonal imbalance biomarkers, as well as genetic- or kidney-derived biomarkers, have also been proposed. Aside from traditional and novel CVD risk factors, additional biomarkers have also been investigated, including cardiac and digestive biomarkers. A recent umbrella review identified 408 unique biomarkers but highlighted the lack of consensus about which additional biomarkers to use in clinical practice. Populations of interest were heterogeneous in terms of age, sex, and CVD risk assessment. Many studies have assessed the potential of various biomarkers to predict CVD and mortality, but most have focused on individuals known to be at high risk for CVD, such as those with a prior CVD history or with symptomatic coronary/intermittent carotid artery territory or peripheral artery disease. Therefore, this systematic review and meta-analysis aimed to assess and summarize the current evidence on the ability of advanced or novel lipoproteins/biomarkers to predict incident CVD among middle-aged adults without a prior CVD history or symptoms, with particular focus on the following issues: 1) novel advanced protocols and assays.